The Effect of Knowledge Sharing on the Performance of Educational Personnel at Universitas Negeri Medan - Harahap, Vivi Ramayanti; Sihombing, Tunggul; Siahaan, Asima Yanty S (International Journal of Business and Applied Economics, 2025)
The objectives of this study are to: 1) identify the knowledge sharing practices of educational staff at Universitas Negeri Medan, 2) assess the performance of educational staff at Universitas Negeri Medan, and 3) explain the influence of knowledge sharing on the performance of educational staff at Universitas Negeri Medan. This research is classified as explanatory research, which examines the relationship between the knowledge sharing variable (X) and the performance variable (Y) of educational staff at Universitas Negeri Medan. The results indicate that knowledge sharing has a positive relationship with performance, as represented by the regression equation Y=15.372+0.2X. The correlation coefficient r=0.49 signifies a moderate relationship between the two variables, with a coefficient of determination of 24.1%, suggesting that knowledge sharing accounts for 24.1% of the variance in performance.